2015
DOI: 10.1098/rsos.140484
|View full text |Cite
|
Sign up to set email alerts
|

First indications that northern bottlenose whales are sensitive to behavioural disturbance from anthropogenic noise

Abstract: Although northern bottlenose whales were the most heavily hunted beaked whale, we have little information about this species in its remote habitat of the North Atlantic Ocean. Underwater anthropogenic noise and disruption of their natural habitat may be major threats, given the sensitivity of other beaked whales to such noise disturbance. We attached dataloggers to 13 northern bottlenose whales and compared their natural sounds and movements to those of one individual exposed to escalating levels of 1–2 kHz up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 31 publications
5
92
0
Order By: Relevance
“…Stimpert et al (2014) observed similar patterns of be havioral response in a Baird's beaked whale to simulated 3− 4 kHz sonar CEEs, although response intensity abated more quickly following exposure in that individual compared to the Ziphius response measured by De Ruiter et al (2013a). These combined results are consistent with the findings of Tyack et al (2011) andMiller et al (2015) in demonstrating clear, strong, and pronounced behavioral changes, including sustained avoidance with associated energetic swimming and cessation of feeding behavior at quite low received levels (~100 to 135 dB re 1 µPa) for exposures with relatively nearby (2 to 5 km) sound sources in simulated sonar CEEs.…”
Section: Socal-brssupporting
confidence: 79%
See 2 more Smart Citations
“…Stimpert et al (2014) observed similar patterns of be havioral response in a Baird's beaked whale to simulated 3− 4 kHz sonar CEEs, although response intensity abated more quickly following exposure in that individual compared to the Ziphius response measured by De Ruiter et al (2013a). These combined results are consistent with the findings of Tyack et al (2011) andMiller et al (2015) in demonstrating clear, strong, and pronounced behavioral changes, including sustained avoidance with associated energetic swimming and cessation of feeding behavior at quite low received levels (~100 to 135 dB re 1 µPa) for exposures with relatively nearby (2 to 5 km) sound sources in simulated sonar CEEs.…”
Section: Socal-brssupporting
confidence: 79%
“…Cox et al 2006). The strong response for a bottlenose whale measured by Miller et al (2015) was particularly striking in that it resulted from a 1−2 kHz sonar signal, which is even further from the species-typical sound production than the 2−7 kHz sonars in the other studies, presented over 5 km from the source in an area where operational military sonars seldom occur. While the CEE results for beaked whales now span 4 different species in different parts of the world, these studies have all involved small sample sizes (1 to 2 individuals per species), and additional experimental work is clearly needed.…”
Section: General Conclusion From Recent Sonar-related Ceesmentioning
confidence: 93%
See 1 more Smart Citation
“…In fact, significant impacts to beaked whales could occur at levels lower, and from sound sources at greater distances from animals, than previously thought, arguably making current US mitigation guidelines for mid-frequency active sonar ineffective at preventing wide-scale impacts to whales. Miller et al (2015) determined that Northern bottlenose whales (Hyperoodon ampullatus) showed a "high sensitivity . .…”
Section: The Received Levels Of Sonar and Beaked Whales Impactsmentioning
confidence: 99%
“…Ray tracing was used to study the impact of the noise from the seismic air guns on fish behavior (Hovem et al, 2012) and to estimate the received sonar signals by the northern bottlenose whales (Miller et al, 2015). Parabolic equation (PE) was also utilized to estimate the sound exposure level to seals around the pile driving location near a wind farm construction site (Hastie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%